Chemical profiling, HPLC characterization and in-vitro antioxidant potential of Pakistani propolis collected from peripheral region of Faisalabad - Shahbaz, Muhammad; Zahoor, Tahir; Arshad, Rizwan; Rafiq, Saima; Qaisrani, Tahira Batool; Liaqat, Atif; Javed, Muhammad Sameem; Akbar, Zainab; Raza, Nighat; Murtaza, Shamas; Farooq, Umar; Imran, Muhammad; et al. (Cellular and Molecular Biology, 2021)
Propolis is a highly adhesive and resinous product of honey bee (Apis mellifera L.) which is produced from the exudations of plants. Bee propolis being a source of bioactive compounds like polyphenols and flavonoids imparts numerous biological properties including, antioxidant, anti-inflammatory, antimicrobial and anticancer activities. Present study was designed to elucidate the composition and antioxidant status of locally available propolis using in-vitro conditions. Propolis collected from locally found apiaries and its hydroalcoholic extract of propolis was prepared using different concentrations of ethanol and methanol. The results regarding proximate composition of propolis showed a higher proportion of ether extract (85.59±0.87%) and lowest contents of crude fiber (0.31±0.08%). Among the mineral's sodium, potassium and calcium was found in a concentration of 11.33±0.91, 52.10±2.9 and 10.53±0.83.59±0.23mg/Kg respectively whilst zinc was noticed as 3.59±0.23mg/Kg. HPLC characterization indicates a highest concentration of Chlorogenic acid 31.80±2.56mg/Kg whereas gallic acid (0.21±0.01mg/Kg) was found in lowest concentration among the polyphenols. Ethanol extract represents more phenolic contents, DPPH activity and antioxidant status as 327.30±14.89mg/gGAE, 73.18±4.43% and 60.59±4.38% accordingly in comparison to methanol and water extract. Bee propolis found an effective source of natural antioxidants which retards the production of free radicals and reactive oxygen species thus help to cope oxidative stress.